The equation is x^2 + 12x - 64 = 0. I think I have the first three steps right:
x^2 + 12x = 0 + 64
4 (x^2) + 4(12x) = 4 (64) or 4x^2 + 48x = 256
then I squared the coefficient of the original x term and added it to both sides
4x^2 + 48x + 12^2 = 256 + 12^2 or 4x^2 + 48x + 144 = 256 + 144
from here I am stuck. I do not understand how to find the square root of both sides
nor do I get the last two steps. Can you please help?
x^2 + 12x = 0 + 64
4 (x^2) + 4(12x) = 4 (64) or 4x^2 + 48x = 256
then I squared the coefficient of the original x term and added it to both sides
4x^2 + 48x + 12^2 = 256 + 12^2 or 4x^2 + 48x + 144 = 256 + 144
from here I am stuck. I do not understand how to find the square root of both sides
nor do I get the last two steps. Can you please help?